Question #38483

1 Answer
Sep 7, 2016

Answer:

#x > (39) / (11)#

Explanation:

We have: #(2) / (3) (6 - x) < (1) / (4) (x + 3)#

First, let's cross-multiply:

#=> 8 (6 - x) < 3 (x + 3)#

Then, let's expand the parentheses:

#=> 48 - 8 x < 3 x + 9#

Next, let's subtract #9# from both sides:

#=> 39 - 8 x < 3 x#

#=> 3 x > 39 - 8 x#

Now, let's add #8 x# to both sides:

#=> 11 x > 39#

Finally, let's divide both sides by #11#:

#=> x > (39) / (11)#

Therefore, the solution to the inequality is #x > (39) / (11)#.